Participatory Equality and Public Policies: the Case of Tourism Management Councils - Frade da Mata, Gilberto Maurício; Emmendoerfer, Magnus Luiz (Anais Brasileiros de Estudos Turísticos, 2017)
This article analyzes the participative equality and the municipal public policies from the cases of municipal tourism management councils of Ouro Preto and Tiradentes, Minas Gerais, Brazil. In the literature, the discussion of participatory equality runs through the analysis of the choice of representatives and the analysis of public policies. In this sense, the question is: what are the prevailing public policy steps and the choice of representatives? For this purpose the objective of this article is to characterize the activities of the counselors as stages of a political cycle and the way they are organized to take decisions on these policies. Methodological procedures were guided by a qualitative approach. He used the multiple case study method. The techniques of data collection included interviews and documentary research. The interpretation of the data came from the categories that emerged of the bibliographic review and the thematic content analysis. The results show that the activities of the counselors, as stages of a political cycle, present distances in development, implementation and evaluation. In both management councils, the convergences between what is expected and observed in terms of public policies only occurs (when it occurs) in the formulation. Non-parity and related representation have been presented as influencing elements that jeopardize the equal opportunity of participation of members of society and government. As contributions the study expands the analysis of participatory equality beyond social management, contemplating conceptual aspects for the analysis of the representation in deliberative space and public policies with tourism as a context of empirical study.